(untitled) (Journal of Economic Research & Business Administration, 2017)
The paper discusses the principles and mechanisms for the development of territorial clusters based on the example of the textile industry of the South Kazakhstan region. Cluster, as an initiative for the development of the region’s economy, attracted much attention around the world. The fact that many governments invest significant resources and efforts in the growth and development of such clusters can be seen as yet another proof of their importance. Kazakhstan is not an exception, therefore in this article integration of the cluster approach into governmental programs and strategies of regional and economic development is considered. The transition to innovative development requires concentration of resources and efforts on the most promising complementary groups of enterprises that can form the innovative potential of the region and have the highest opportunities for increasing competitiveness. Formation and development of clusters is an effective mechanism for regional development, facilitating the attraction of foreign direct investment and enhancing foreign economic integration.